Leukocytapheresis in patients with inflammatory bowel diseases - Woźniak, Małgorzata; Kurnatowska, Ilona; Małecka-Panas, Ewa; Talar-Wojnarowska, Renata (Gastroenterology Review/Przegląd Gastroenterologiczny, 2021)
Leukocytapheresis, a blood purification therapy, exerts anti-inflammatory effects by removing activated leukocytes from the peripheral blood through extracorporeal circulation. It is a potential option of treatment for patients with inflammatory bowel diseases (IBD), especially those with ulcerative colitis (UC), who do not respond to conventional therapy. Given that it has a favourable safety profile and seems to have steroid sparing effects, its position in the treatment of UC is likely to expand. However, there is inadequate evidence to draw any conclusions about the efficacy of leukocytapheresis in patients with Crohn’s disease, and it should only be used in accordance with special arrangements for consent. Considering the current level of knowledge, it is essential to conduct large, well-designed, randomized clinical trials to evaluate the effects of leukocytapheresis in the management of IBD patients.